Speed of Retrenchment Strategies of Family Firms in Times of Crisis - Moreno-Menéndez, Ana M.; Pérez-Reina, Concepción; Ramos-García, Alicia (European Journal of Family Business, 2023)
This paper analyzes how fast do family businesses react to a decline in their financial performance. Turnaround is especially relevant in family businesses due to the importance of non-economic goals. We study the differences between family and non-family businesses in relation to closure and recovery speed, and the role of firm age and size as contingent factors. The empirical research analyzes panel data comprising more than 23,000 declining Spanish firms, over an eleven-year period (2006-2016). Our findings show that family businesses will close earlier than non-family businesses without significant difference between family and non-family businesses recovery speed